MENYOAL METODE FATWA KEUANGAN DAN PERBANKAN SYARIAH INDONESIA - Etik Hawiati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2014)
Fatwa in economic perspective and economic banking are given by National Dewan of Syariah (DSN) which is not able to cover all aspiration of multi religion in Indonesia. In other side, Fatwa from DSN is should be done by all actors of economic and economic banking in Indonesia. This writing is to examine critically for the method of Ifta’ DSN-MUI (Ulama Council of Indonesia). In this process of examination will be operated by three steps, they are to reconstruct of method, which are used by DSN. To compare the method of ifta>’ DSN by general method, which is used by other ulama, and to examine a context of fatwa, used contemporary approach in Islamic law. By using library research, it can be conclude that there are some weaknesses especially in the method of ifta>’, and the classical method from DSN cannot able to give fatwa for syari’ah financial in modern era. Still there is unmatched between fatwa and practicing in middle of society.